Obesity as a Source of Endogenous Compounds Associated With Chronic Disease: A Review. (24th March 2020) - Smith, Carr J; Perfetti, Thomas A; Hayes, A Wallace; Berry, Sir Colin
Abstract: In 2014, it was estimated that more than 1.9 billion adults were overweight with over 600 million classifiable as obese. Approximately two-thirds of U.S. adults over 20 years of age are currently overweight with about 35% classified as obese, a figure thought likely to reach 42% by 2030 in those over 18 years of age. Adipose cells from stored body fat secrete estrogen and a very large number (> 500) of biologically active substances termed adipokines, in addition to inducing, by other cell-driven effects, pathological alterations in insulin pathways. The U.S. National Cancer Institute reports that exposure to the hormone disrupting and proinflammatory effects of excess adipose tissue are associated with an increased risk for 11 different cancers. Obesity is also associated with a number of serious non-neoplastic conditions including metabolic syndrome and type 2 diabetes; menstrual cycle irregularities and lowered fertility (men and women); and abnormal bone morphology in a subset of female patients. In men hypogonadism, low testosterone levels, benign prostatic hyperplasia, and lowered sperm counts have been reported. In developed countries, the endogenous adverse health burden associated with obesity is only matched, quantitatively and qualitatively, by the exogenous toxicity of cigarette smoking. The investigation of possible hormonal and/or proinflammatory effects of chemicals should include an assessment of the profound endocrine alterations associated with obesity.